The adaption of promising rubber clones in the central highlands of Vietnam - Tuy L M; Duong P H; Hoa T T T; Lam L V; Phuc L G T (IRRDB Symposium on Natural Rubber(Hevea brasiliensis) V.1- General, Soils and Fertilization and Breeding and Selection Sessions. Ho Chi Minh City, Vietnam, 14-15 October 1997,p155-163)
The Central Highlands of Vietnam are characterized by some distinct factors that limit the performance of rubber trees: (a) the altitude is high from 350 to 800m above sea level (ASL); (b) there are regular strong winds in the long dry season, lasting 5-6 month annually, followed by a rainy season in which rainfall can last some few days; (c) there are low temperatures in a few months of the dry monsoon season when the absolute minimum temperature is from 5.5 to 7 degree C; (d) the area is hilly and (e) Oidium is the most important disease, others are Phytophthora leaf fall and black stripe. For comparison, the two main rubber growing regions are categorised into four sub-regions in the order of the most favourable to most marginal conditions for rubber: SE1 and SE2 for the Southeast and HL 1 and HL 2 for the Highlands. The data used is from 8 Large Scale Clonal Trials (LSCT), 1 Small Scale Clonal Trial (SSCT) in the Highlands and 12 LSCT in the Southeast. In terms of growth, the immature period could be less than six years in SE 1 but the period was half to one year longer in SE2. In HL1 (below 600m ASL), the period was the same as for SE1 but the period was half to one year more in HL2 (above 600m ASL, 7.5 to 8 years). For latex yield, the trend is the same as for growth. In general, the performance of rubber clones in the Highlands was lower than that in the Southeast region. However, some clones, namely GT 1 and RRIC 110, were more stable than others in both growth and yield. In terms of girth at seven years old in all regions, GT 1 and RRIC 110 were the lowest in CV;(7.48-6.69;) and PB 235 and VM 515 were the highest (12.74-11.24;). In terms of the cumulative yield of 12 years of old trees (5-6 years of tapping), RRIC 110 was the highest yielder among the clones tested in HL 1, the same yield as in SE2 (99.6;); GT 1 was not a high yielder but the yield was also the same as in SE2 (99.9;). Some high yielding clones were still better in HL 1 but the yields were decreased compared with those in SE2: 93.5, 85.8 and 72.0;for PB 235, VM 515 and PB 255, respectively (kg/ha/4-5 years). In one SSCT at HL2, PB 235 and VM 515 were not the best clones and had a lower yield than RRIM 600 and GT 1 (by 15-20;mean yield in g/t/t over the first three years of tapping) although some of the other clones gave a better performance than the GT 1 and RRIM 600 control clones. Among the most promising clones, PB 312, PB 280, RRIC 101 and RRIC 130 gave a yield (g/t/t) from 100 to 146;over GT 1 whilst PB 260, LH 83/0215, PBIG 14/51, PB 311, PBIG 12/81, RRIM 712 gave a yield from 71 to 97;over GT 1. The mean yield of the first three years of tapping was 21.49 g/t/t for Gt 1 and 32.79 g/t/t for RRIM 600 whereas the promising clones gave yields from 36.69 g/t/t (RRIM 712) to 52.89 g/t/t (PB 312). These elite clones also suffered only light infection with Oidium leaf disease.
Keywords: Rubber clones; Vietnam